TINDAK TUTUR ILOKUSI DALAM NOVEL ANNOYING BOY KARYA INESIA PRATIWI - Fadhilah, Rizki; Patriantoro, Patriantoro; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe researcher chose illocutionary speech acts as the main focus of the research, the type of the speech that was often found in everyday life. The problems discussed in this research were the forms of illocutionary speech acts in the novel of Annoying Boy by Inesia Pratiwi and its application in teaching and learning process in the school. The aims of this research were to describe and analyze the forms of illocutionary speech acts in the novel of Annoying Boy by Inesia Pratiwi. The results of the description and analysis between the speakers and the interlocutors contained in Inesia Pratiwi's Annoying Boy novel were: 1) assertive speech acts included suggesting, declaring, boasting and complaining; 2) directive speech acts included ordering, commanding, pleading, advising, and recommending; 3) expressive expression of speech acts included thanking, congratulating, apologizing, blaming and praising; 4) commissive speech acts included promising and offering; and 5) the declaration of speech acts included naming, ostracizing and punishing. Based on the results of the analytical of illocutionary speech acts in the novel of Annoying Boy could be applied in the learning process in the school as a modeling text. Keywords: Illocutionary Speech Acts, Annoying Boy Novel, Conversation